PENGARUH BAURAN PEMASARAN RITEL TERHADAP KEPUTUSAN PEMBELIAN PRODUK DI HYPERMART PONOROGO CITY CENTER - DWIRACHMAWATI, MEITA (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
Ponorogo is a cultural city that is dominated by traditional markets. As the development of modern society, in September 2013 Hypermart open the 90th outlets in Ponorogo City Center which is the first mall in Ponorogo. Hypermart comes with the most complete retail marketing mix, that is product, price, promotion, store design, merchandise presentation, customers service, and location. It is an interesting phenomenon to be researched, whether modern marketing stimuli presented by Hypermart in Ponorogo will get a good response as well as in other major cities. This research is a quantitative research with a survey approach to determine the influencet of retail marketing mix towards product buying decision in Hypermart Ponorogo City Center. This research is done at 120 respondents to do assumption classical test and hypothesis test. The result of F-test show as big as 20,268 and supported by the signification value 0,000 which is indicated that there simultaneously there is an influence of retail marketing mix towards product buying decision in Hypermart Ponorogo City Center. the result of t-test partially indicated that variables product(X1), price(X2),promotion(X3),store design(X4), and customers service(X6) had the significant influence of retail marketing mix towards buying decision in Hypermart Ponorogo City Center, while the variable merchandise presentation(X5) and location(X7)had no effect. The value of Adjusted R Square 0,531 means that retail marketing mix influence of product buying decision in Hypermart Ponorogo City Center as big as 53,1% while the remainingas big as 46,9% are influenced by the other variables outside of this research. Keywords: retail marketing mix, buying decision.